THE EFFECT OF CONSTRUCTING AND ANALYZING MODEL IN ENHANCING TERTIARY EFL LEARNERS’ GRAMMAR AND WRITING ABILITY - Mufanti, Restu; Susilo, Andi; Gestanti, Rohfin Andria; Nimasari, Elok Putri (PEOPLE: International Journal of Social Sciences, 2019)
This research aimed at examining the effect of Constructive and Analyzing Model on learners’ grammar mastery and writing ability at the university EFL context. The study also attempted to seek the light on how they perceived about the implementation of the model in learning grammar integrated with writing activities. A quasi-experimental with pretest–posttest non-equivalent control group design was employed, involving 49 university learners. Cloze-grammar tests and questionnaire were used to collect the data. Before administered, the instruments were tried out in a pilot class to establish validity and reliability. The experiment group was engaged in CAM activities following five major phases, such as text observation, form/function and discourse connection, grammar exploration, peer and reflective feedback, and comprehension check and clarification, meanwhile the control group received no treatment and was taught by using an ordinary method. The independent sample t-test was performed using SPSS 25 to investigate the difference of grammar mean score between these two groups in terms of S-V agreement and tenses. The results revealed that the Sig. (2-tailed) values of the experiment group and the control group were .015 and .586 respectively, and the significance value between the groups was .039. The findings showed that there was a significant difference on the grammar score between the experimental group and the control group. It revealed CAM could assist learners not only to understand grammar lesson more easily but also to make a use of their grammatical knowledge in writing more accurately. Furthermore, most of the participants perceived positively towards the implementation of CAM in learning grammar. Since the implementation of CAM is effective in grammar class, ELT practitioners are suggested to apply this model on other skills in different areas.